Mass propagation for electromagnetic Schrödinger evolutions. (April 2022) - Barceló, Juan Antonio; Cassano, Biagio; Fanelli, Luca
Abstract: We investigate the validity of Gaussian lower bounds for solutions to an electromagnetic Schrödinger equation with a bounded time-dependent complex electric potential and a time-independent vector magnetic potential. We prove that, if a suitable geometric condition is satisfied by the vector potential, then positive masses inside of a bounded region at a single time propagate outside the region, provided a suitable average in space–time cylinders is taken.